Promotion of innovative startups - Some assessments and recommendations for policy making - Dinh, Dang Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
After presenting basic contents of innovative startups, ecosystem of startups and specific features of innovative startups, the paper provides analysis of lessons learnt from some nations for policies to promote innovative startups. The main content of the paper is focused on analysis of actual situation of policies for promotion of startups in Vietnam, their remaining problems and challenges. Further, the paper proposes some solutions to promote startups in Vietnam, particularly the needs of a set of indicators for assessment of policies for promotions of innovative startups, and a hint for a breaking-through solution to exploit and to commercialize knowledge sources in universities. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">